PENINGKATAN KINERJA KARYAWAN DENGAN PELATIHAN MELALUI KOMPETENSI - MUHTADIN, ZIYADATUN; FRIANTO, AGUS (Jurnal Ilmu Manajemen (JIM), 2019)
The purpose of this research is analyzed about employee performance effected by training through competency. Causality research using quantitative approach. The sampling technique using samples saturated by the number of 40 respondents at PT Pos Indonesia (Persero) Cabang Surabaya Selatan. This research used Structural Equation Model (SEM) with the assistance of smartPLS 3.0 software as the statistics analysis. The results of this research show that employee performance is not effected by training, competence effected by training significantly and positively, employee performance effected by competence significantly and positively, and competence can be an intervening variable between training on employee performance.